2020
DOI: 10.1111/eci.13353
|View full text |Cite
|
Sign up to set email alerts
|

Noxa upregulation and 5‐gene apoptotic biomarker panel in colorectal cancer

Abstract: Background NOXA and MCL1 are involved in the intrinsic pathway of apoptosis, where Noxa selectively binds to MCL1 and prevents it from inhibiting apoptosis. Both factors are considered as potential tumour biomarkers, while MCL1 has attracted interest as target in cancer. The purpose of this study was to investigate the expression of NOXA and MCL1 in 160 CRC tumour samples, to investigate their significance, also in combination with IAPs, DR5 expression and KRAS gene mutations in CRC. Materials and methods Fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Targeting ALOX5 promotes colorectal cancer cell proliferation, and silencing of ALOX5 inhibited colorectal cancer cell growth [ 28 , 29 ]. PMAIP1 is involved in the intrinsic apoptosis pathway, selectively binds to MCL1, and prevents MCL1 to inhibiting apoptosis in colorectal cancer [ 30 ]. EGR1 high expression correlates with resistance to anti-EGFR treatment in metastatic colorectal cancer patients treated with cetuximab, and silencing EGR1 expression promotes killing HCT116 colorectal cancer cells and delaying tumor growth [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting ALOX5 promotes colorectal cancer cell proliferation, and silencing of ALOX5 inhibited colorectal cancer cell growth [ 28 , 29 ]. PMAIP1 is involved in the intrinsic apoptosis pathway, selectively binds to MCL1, and prevents MCL1 to inhibiting apoptosis in colorectal cancer [ 30 ]. EGR1 high expression correlates with resistance to anti-EGFR treatment in metastatic colorectal cancer patients treated with cetuximab, and silencing EGR1 expression promotes killing HCT116 colorectal cancer cells and delaying tumor growth [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inherent challenges of delayed diagnosis and the high propensity for metastasis in gastric cancer contribute to elevated mortality rates, with a median survival rate of less than 1 year for patients with metastatic gastric cancer 37 . Cancer cells exhibit marked genetic and epigenetic alterations, frequently instigating the initiation and progression of malignancies by perturbing the molecular and cellular processes governing cancer cells 38 . Consequently, a comprehensive exploration of the molecular and cellular mechanisms underpinning the pathogenesis of gastric cancer is imperative for precise diagnosis, prognostic assessment, and therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are commensurate with our hypothesis that functional NOXA is important in the execution of successful apoptosis in response to therapy, and that a decline in NOXA expression following therapy is likely to be associated with suboptimal responses to chemotherapy 15 , 28 . In other cancers, Kosmidou et al reported that NOXA mRNA was overexpressed in 66% of the examined colorectal cancer tumor samples relative to their paired non-malignant colonic tissue counterparts 45 . However, the authors performed IHC staining for NOXA protein in 39 samples that “showed high levels of differential mRNA expression” 45 , but found negative NOXA expression in some cases and did not report detailed findings on the IHC staining, suggesting that the IHC approach might be a better assay than mRNA expression for NOXA detection.…”
Section: Discussionmentioning
confidence: 99%
“…In other cancers, Kosmidou et al reported that NOXA mRNA was overexpressed in 66% of the examined colorectal cancer tumor samples relative to their paired non-malignant colonic tissue counterparts 45 . However, the authors performed IHC staining for NOXA protein in 39 samples that “showed high levels of differential mRNA expression” 45 , but found negative NOXA expression in some cases and did not report detailed findings on the IHC staining, suggesting that the IHC approach might be a better assay than mRNA expression for NOXA detection. Unfortunately, further evidence on the evaluation of NOXA protein expression levels in clinical cancer samples is parsimonious.…”
Section: Discussionmentioning
confidence: 99%